All rock and roll is homosocial: the representation of women in the British rock music press - Davies, Helen (Popular Music, 2001)
The British rock music press prides itself on its liberalism and radicalism, yet the discourses employed in music journalism exclude women from serious discussion both as musicians and as fans. In particular, the notion of credibility, which is of vital importance to the ‘serious’ rock music press, is constructed in such a way that it is almost completely unattainable for women.The most important and influential part of the British music press was until recently its two weekly music papers, Melody Maker (MM) and the New Musical Express (NME), both published by IPC magazines. The NME, launched in 1949, contains reviews, concert information and interviews with performers and describes itself as ‘a unique blend of irreverent journalism and musical expertise’ (www.ipc.co.uk). MM, which started life in 1926 as a paper for jazz musicians, had similar content but a greater emphasis on rock, as opposed to pop, music. It was relaunched in 1999 as a glossy magazine, before ceasing publication or, as IPC put it, merging with the NME, in December 2000.
Publisher: Cambridge University Press